Manufacturing of Fired Clay Bricks for Internal Walls with Dolomite Residue as a Secondary Material - Nurmurat Kandymov; Serdar Korpayev; Serdar Durdyev; Rejepmyrat Myratberdiyev; Leyla Gurbanmyradova (Buildings, 2023)
Alternative materials need to be mapped, characterized, and valued in order to reduce clay usage. A study was conducted on the utilization of waste dolomite material from a mirror manufacturing factory in the production of bricks where the factory disposes 2500 tons of dolomite waste annually. Dolomite residue was mixed with clay raw material in various mass ratios of 90/10, 87.5/12.5, 85/15, and 82.5/17.5 wt%, extruded with proper moisture content, dried at 110 °C, and fired at 1000 °C and 1100 °C. The addition of dolomite resulted in an efflorescence on the surface of the bricks while also providing thermal insulation advantages and higher fire resistance. The addition of dolomite allowed for an increase in firing temperature to 1100 °C, which was initially not possible due to the melting characteristics of the clay. Dolomite also decreased the density of the bricks, which is crucial in order to decrease the dead load in structures. The produced bricks are intended for internal wall applications because of the efflorescence on the surface of the bricks. Overall, the addition of dolomite improved thermal conductivity and density, and other characteristics also showed suitable results.